2022
DOI: 10.1111/apm.13218
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 and PD‐1 expression in thyroid follicular epithelial dysplasia: Hashimoto thyroiditis related atypia and potential papillary carcinoma precursor

Abstract: Programmed cell death ligand (PD-L1)/PD-1 expression has been studied in a variety of cancers and blockage of PD-L1/PD-1 pathway is a cornerstone of immunotherapy. We studied PD-L1/PD-1 immunohistochemical expression in 47 thyroid gland specimens in groups of (1) Hashimoto thyroiditis (HT) only; (2) HT and follicular epithelial dysplasia (FED); and (3) HT, FED, and papillary thyroid carcinoma (PTC). PD-1 positivity was found in immune cells, namely in lymphocytes, macrophages, and plasma cells with mean values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…A recent phase II single-arm study of spartalizumab, a PD-1 inhibitor, showed a favorable ORR of 29% in PD-L1 (+) vs. 0% in PD-L1 (–) ATC patients (n=42); the highest rate of response was observed in the subset of patients with PD-L1 ≥ 50% (6/17; 35%); median PFS and OS are 1.7 and 5.9 months, respectively; OS also correlated with PD-L1 status, with a median OS of 1.6 months in patients with PD-L1 < 1%, compared with not yet reached in PD-L1(+) patients ( 106 ). Notably, the co-existence of thyroid cancer with thyroiditis is common, and PD-L1 expression can also be detected in inflammatory thyroid tissue ( 107 ). Therefore, it should be cautious to interpret PD-L1 expression for thyroid cancer combined with thyroiditis and more investigations are needed.…”
Section: Landscape Of Treatment In Dedifferentiated Thyroid Cancermentioning
confidence: 99%
“…A recent phase II single-arm study of spartalizumab, a PD-1 inhibitor, showed a favorable ORR of 29% in PD-L1 (+) vs. 0% in PD-L1 (–) ATC patients (n=42); the highest rate of response was observed in the subset of patients with PD-L1 ≥ 50% (6/17; 35%); median PFS and OS are 1.7 and 5.9 months, respectively; OS also correlated with PD-L1 status, with a median OS of 1.6 months in patients with PD-L1 < 1%, compared with not yet reached in PD-L1(+) patients ( 106 ). Notably, the co-existence of thyroid cancer with thyroiditis is common, and PD-L1 expression can also be detected in inflammatory thyroid tissue ( 107 ). Therefore, it should be cautious to interpret PD-L1 expression for thyroid cancer combined with thyroiditis and more investigations are needed.…”
Section: Landscape Of Treatment In Dedifferentiated Thyroid Cancermentioning
confidence: 99%
“…In addition, its ligand PD‐L1 is also abnormally high expressed in tumor cells, which is also a major factor promoting tumor immune escape ability 12 . The expression of PD‐L1/PD‐1 in various cancers has been studied, and blocking the PD‐L1/PD‐1 pathway is the cornerstone of immunotherapy 13 . Therefore, it is important to understand the specific mechanism of PD‐L1 in immune escape in TC.…”
Section: Introductionmentioning
confidence: 99%
“… 12 The expression of PD‐L1/PD‐1 in various cancers has been studied, and blocking the PD‐L1/PD‐1 pathway is the cornerstone of immunotherapy. 13 Therefore, it is important to understand the specific mechanism of PD‐L1 in immune escape in TC.…”
Section: Introductionmentioning
confidence: 99%